Analisis kesalahan dalam keterampilan menulis tegak bersambung pada peserta didik kelas ii sekolah dasar - Alfi Nisrina Nur Ahlina; Sukarno Sukarno; Fadhil Purnama Adi (Universitas Sebelas Maret, 2019)
This research is a descriptive qualitative study with a single case study approach. This research was conducted because there are many errors in handwriting skills. This study aims is to analyze errors in handwriting skills in 2nd grade students of SD Negeri Tunggulsari 1 No. 72 Surakarta academic year 2018/2019. The sample is determined by purposive sampling technique with certain considerations and objectives. The research data was collected through interviews, observation and documentation which were then analyzed based on indicators. Error analysis is carried out based on indicators of writing error and the aspect. The results of this study found that writing errors consist of letter formation errors, spacing errors between letters and words, slant consistency errors, size and proportion, legibility, and neatness of handwriting by 2nd grade students. The most mistake is found in the formation, size and propotion, and also the error of spacing between letters and words. While errors in legibility, neatness and consistency of writing slant are rarely found in the work of students.